Study on Reduction of Water Fins in the Middle Pier of the Spillway of Miaotang Reservoir - FU Xuhui; LIU Zhiqing; GONG Ao; LUO Yuanyuan; DIAO Yunchuan; HU Guangping (Renmin Zhujiang)
The water fin phenomenon is a common hydraulic phenomenon behind the piers in the gate chambers of discharge structures such as spillways and spillway tunnels.Considering the serious water fin phenomenon at the tail of the middle pier of the spillway of Miaotang Reservoir,a model test with a scale of 1:30 is used to compare and study the three types of middle piers.The results reveal that the water flow of two holes meets and collides behind the elliptical middle pier of Type 1 to form a large-scale water fin.The middle pier of Type 2 has a limited effect in reducing the water fins at the tail of the pier in the spillway,and strong collision still occurs behind the pier.The front and rear ends of the tail middle pier of Type 3 are connected by streamlined curves to ensure that the water flows smoothly along the streamlined surface of the tail pier,and thus sudden changes in flow speed can be avoided to effectively reduce the scale of the water fin.In this way,the discharge flow is smooth,and the discharge flow pattern is significantly improved.The research results can provide a reference for similar engineering.